Unradiogenic reactive phase controls the εNd of authigenic phosphates in East Antarctic margin sediment. (1st March 2023) - Creac'h, Layla; Noble, Taryn L.; Chase, Zanna; Charlier, Bruce L.A.; Townsend, Ashley T.; Perez-Tribouillier, Habacuc; Dietz, Christian
Abstract: Determining past changes in ocean circulation on the Antarctic margin is important for understanding the interactions between climate, circulation, and ice sheet retreat. However, the application of neodymium isotopes (εNd ), a well-known proxy of ocean circulation, is limited on the Antarctic margin, due to the lack of carbonate preservation and inconsistency in authigenic εNd leached from bulk sediment. Here we assess the use of the εNd proxy along the continental rise of Wilkes Land, by combining analyses of seawater with phases extracted using a 10-second reductive leach in co-located surface sediments. Dissolved seawater εNd values displayed the following water mass signatures; εNd  = −8.8 ± 0.2 (n = 1) for Antarctic Surface Water; εNd  = −9.7 ± 0.2 (n = 2) for Winter Water; and εNd  = −8.7 ± 0.3 (n = 6) for modified Circumpolar Deep Water. The sediment leachate did not reproduce a bottom water Nd signature and yielded a very variable εNd, ranging from −10.4 to −14.4. In contrast, the bulk detrital sediment εNd fell within a narrow range of −13.1 ± 0.5 (n = 29). Examination of elemental ratios and rare earth element (REE) anomalies indicates that the leaching procedure extracts exclusively authigenic phases. The strong relationship found between phosphorus (P) and REE suggests that a P-associated phase is the main REE host-phase leached, as opposed to ferromanganese oxyhydroxides. The leached europium anomalies and εNd indicate that the extracted Nd signature is influenced by two end members, one with a seawater-like εNd (∼-8) and one more negative than the bulk detritus (εNd ∼−14). Finally, the decoupling between [Nd] and εNd, as well the distinct middle-REE enrichments measured in the leach implies the authigenic εNd is controlled by diagenesis. We thus infer that the Nd signature of the leached phosphates is derived from porewater and influenced by the presence of a reactive detrital component in the sediment. Unradiogenic reactive sedimentary phases which easily dissolve into porewaters are likely sourced from the subglacial erosion of ancient metasediments and crustal remnants on the Wilkes Land coast. These new εNd data contribute to the evaluation of the εNd proxy at complex, dynamic and under-studied interfaces such as the East Antarctic margin. However, further work is still needed to develop reliable proxies of past Antarctic water masses.